THE USE OF VIDEO AND E-BOOKLETS IN EDUCATING PARENTS ON SIBLING RIVALRY - Cantika Brilliana; Endah Kamila Mas’udah; Erni Dwi Widyana (SEAJOM: The Southeast Asia Journal of Midwifery, 2022)
Lack of awareness of parents in providing a good role for children can lead to sibling rivalry behavior. Sibling rivalry behavior can be overcome with a good parental role, one of which is by providing appropriate educational media, namely video educational media and e-booklet educational media. This study aims to determine the differences between video educational media and e-booklets on the role of parents regarding sibling rivalry in a early childhood learning center. The research method uses a quasi-experimental nonequivalent control group design. The sample in this study used the total sampling technique, namely 32 respondents who met the sample criteria. Data collection by dividing educational media groups, videos and e-booklets. Each group was given a pretest, then given educational media within seven consecutive days and the role of parents was measured using a questionnaire. Data analysis used the Wilcoxon test and the Mann-Whitney test. The Wilcoxon test results obtained an Asymp.Sig (2-tailed) value of 0.000 <0.05, which means that there is an influence of providing video educational media and e-booklet educational media on increasing the role of parents regarding sibling rivalry in early childhood. And the results of the Mann-Whitney test obtained a value of (2-tailed) 0.264 <0.05, which means that there is no difference between video educational media and e-booklets on the role of parents regarding sibling rivalry in early childhood. Based on the results of the research, video educational media and e-booklets should be considered as additional information and changes in the role of parents.